2017
DOI: 10.1111/cdev.12987
|View full text |Cite
|
Sign up to set email alerts
|

Sometimes It's Good to be Short: The Serotonin Transporter Gene, Positive Parenting, and Adolescent Depression

Abstract: In threatening environments, the short (S) allele of 5-HTTLPR is proposed to augment risk for depression. However, it is unknown whether 5-HTTLPR variation increases risk for depression in environments of deprivation, lacking positive or nurturant features. Two independent longitudinal studies (n = 681 and 176, respectively) examined whether 5-HTTLPR moderated associations between low levels of positive parenting at 11-13 years and subsequent depression at 17-19 years. In both studies only LL homozygous adoles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 86 publications
0
5
0
Order By: Relevance
“…This finding suggests a dominant G×E effect for concurrent social skills, in which the dominant L allele, rather than the S allele, confers susceptibility to the environment. Several recent studies have found an L-allele driven effect (e.g., Little et al, in press), although findings are mixed (Weeland, Overbeek, de Castro, & Matthys, 2015). Divergent findings have been attributed to differing G×E pathways by allele, in which either the S or L allele confers environmental susceptibility depending on the type of environment and developmental outcome assessed (see Weeland et al, 2015).…”
Section: Discussionmentioning
confidence: 98%
“…This finding suggests a dominant G×E effect for concurrent social skills, in which the dominant L allele, rather than the S allele, confers susceptibility to the environment. Several recent studies have found an L-allele driven effect (e.g., Little et al, in press), although findings are mixed (Weeland, Overbeek, de Castro, & Matthys, 2015). Divergent findings have been attributed to differing G×E pathways by allele, in which either the S or L allele confers environmental susceptibility depending on the type of environment and developmental outcome assessed (see Weeland et al, 2015).…”
Section: Discussionmentioning
confidence: 98%
“…A large body of reviews and empirical studies investigating the association of parenting and adolescent depression showed that warmth, care, acceptance and other positive parenting behaviors were negatively linked to depression (Milevsky et al, 2007; Brand et al, 2009a,b; Yap et al, 2014; Wang Y.C. et al, 2015; Little et al, 2017), while negative parenting characterized by harsh, control and neglect were risks for depression (Aunola et al, 2013; Reising et al, 2013; Frazer and Fite, 2016; Murdock et al, 2018). Regardless of the differences in dimension of parenting practice, there is consistency that parental care and control have a close association with individual depression.…”
Section: Introductionmentioning
confidence: 99%
“…While disengaged parenting may not provide children ample guidance and support to manage their emotions, disengaged parents’ lack of harsh, punitive responses to children’s emotions may buffer their children from the more severe negative outcomes. It is worth considering that the absence of parenting practices which are optimal for children’s emotion competence, versus the presence of parenting practices found to have a negative impact on children’s emotion competence, likely has distinct developmental impacts on children’s emotion competence ( Little et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%